ANALYSIS OF SMALLHOLDER CROP FARMERS’ ADAPTIVE CAPACITY AND CONSTRAINTS TO CLIMATE CHANGE RESILIENCE IN MAIGANA AGRICULTURAL ZONE, KADUNA STATE, NIGERIA - Daikwo, O. C.; Saleh, M. K.; Owolabi, J. O.; Shehu, A. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
This study examined the smallholder crop farmers’ adaptive capacities and constraints to climate change resilience in Maigana Agricultural zone, Kaduna State, Nigeria. A multistage sampling procedure was employed to select crop farmers, beginning with the purposeful selection of the Maigana agricultural zone due to its high crop production potential. Subsequently, three Local Government Areas (Kubau, Makarfi, and Soba) were chosen, followed by the selection of fifteen communities. A reconnaissance survey estimated a total of 600 smallholder crop farmers, and using the Yamane (1967) Slovin formula, 252 farmers were randomly selected for the study. Data were collected using structured questionnaires administered to smallholder crop farmers. Descriptive statistics was used to analyse the data, including the mean, frequency distribution, standard deviation, coefficient of variation, and percentages. The findings reveal that 90.2% of respondents were aware of climate change, which is crucial for adaptation efforts. Farmers employ various coping strategies, such as mixed cropping (13.3%), crop diversification (12.9%), and irrigation farming (12.8%), among others. These strategies reflect farmers’ adaptive capacity and resilience. However, significant constraints hinder effective adaptation, including inadequate finance (20.4%), high input costs (16.9%), limited knowledge and information (16.9%), and unfavourable government policies (14.5%). The study concludes that while there is a high level of climate change awareness among smallholder farmers, significant barriers impede their adaptation capacities. To enhance resilience and ensure sustainable agricultural practices, the study recommends developing robust institutional frameworks and supportive policies, improving access to essential resources and advanced technologies, and promoting sustainable agricultural practices through tailored training programmes and workshops.